(untitled) (Ibrahim Cardiac Medical Journal, 2017)
Background & Objective: Postoperative surgical site infections (SSIs) are still among the most common serious complications of surgery in terms of cost and consequences. Different risk factors like age, sex, nutrition, immunity, operation type, duration of stay in hospital and presence of hair on the skin may involve with SSIs. This study was intended to determine the risk factors for surgical site infections in a tertiary level hospital. Methods: This Cross Sectional observational study was carried out in the Department of Surgery, Rajshahi Medical College Hospital, Rajshahi, over a period of 12 months from May 2009 to April 2010. A total of 232 patients (aged 18 years onwards) of either sex scheduled for elective operation were included in the study. Common indications for operation were chronic calculus cholecystitis, stoma in situ, inguinal hernia, renal/urinary stones and benign prostatic hyperplasia and so on. As two patients were discharged on request on 2nd postoperative day, 230 patients were left for final analysis. The patients were followed till discharge. Results: Of the total 230 patients, 21(9.1%) developed post-operative wound infection. The incidence of wound infection was significantly higher in older patients (p = 0.014). However sex did not have any influence on wound infection. The malnourished patients (underweight in terms of BMI) developed SSIs more frequently than their normal or overweight counterparts (p < 0.001). Diabetic patients developed post-operative wound infection more often than the non-diabetics(p = 0.072). The incidence of post-operative wound infection was not found to be associated with shaving of hair on the skin over the operative site (p = 0.378). Contaminated wounds encountered SSI significantly more than the clean wounds did (p = 0.001). Conclusion: The study concluded that one in every ten patients undergoing abdominal surgery may develop postoperative wound infection and factors commonly associated with wound infection are older age, underweight, diabetes, contaminated wound, longer preoperative and postoperative hospital stay. The study suggests that reducing the factors of SSI (as far as practicable) will reduce the incidence of SSI. Ibrahim Card Med J 2015; 5 (1&2): 15-20